Pricing and calibration of Libor Market Model - Pozsonyiová, Daniela; Kolman, Marek; Diviš, Martin; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2018)
This thesis focuses on models of interest rate, especially LIBOR market model. It presents the interest rate theory, interest rate derivatives and most important models of the interest rate. The LIBOR market model is calibrated to real market data. A pricing of a European swaption is performed according to Hull-White model and according to LIBOR market model, the results are compared. A Bermudan swaption is priced with the same models, which requires a different approach and the results are compared again.
Vedoucí práce: Marek Kolman
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: finanční inženýrství [obor dipl. práce]; diplomové práce; master's theses